Trakeidien poikkileikkausdimensioiden jakaumia kuusen rungon eri osissa - Havimo, Mikko; Rikala, Juha; Sirviö, Jari; Sipi, Marketta (Metsäntutkimuslaitos, 2008)
Seloste artikkelista: Havimo, M., Rikala, J., Sirviö, J. & Sipi, M. 2008.. Distributions of tracheid cross-sectional dimensions in different parts of Norway spruce stems. Silva Fennica 42(1): 89–99.
Tutkimusseloste